Harm reduction : a new direction for drug policies and programs - Erickson, Patricia G.; Riley, Diane M. (Diane Mary), 1953-; Cheung, Yuet-wah, 1952-; O'Hare, P. A. (Patrick Anthony), 1947- (University of Toronto Press, 1997)
This edited collection provides the latest in research and critical thinking on public health alternatives to conventional criminal approaches aimed at limiting the harms of both legal and illegal drugs for users and society.
"Collection of papers drawn from 7 international conferences on harm reduction."
"Selected, revised papers originally presented at the fifth International Conference on the Reduction of Drug Related Harm held in Toronto, Canada, 6-10 March 1994"--Introduction.
Keywords: Drug abuse -- Prevention -- Congresses.; Drug abuse -- Treatment -- Congresses.; Drug abuse -- Government policy -- Congresses.; Drug abuse -- Congresses.; Social problems.; Drug abuse -- Social aspects -- Congresses.; Harm reduction -- Congresses.; Drug and Narcotic Control; Substance-Related Disorders -- rehabilitation; Legislation, Drug; Public Policy; Social Problems; Toxicomanie -- Congrès.; Toxicomanie -- Politique gouvernementale -- Congrès.; Toxicomanie -- Traitement -- Congrès.; Toxicomanie -- Prévention -- Congrès.; Problèmes sociaux.; Toxicomanie -- Aspect social -- Congrès.; Réduction des méfaits -- Congrès.; social issues.; POLITICAL SCIENCE -- Public Policy -- Social Security.; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; Harm reduction; Drug abuse -- Social aspects; Social problems; Drug abuse; Drug abuse -- Government policy; Drug abuse -- Prevention; Drug abuse -- Treatment; Conference papers and proceedings